2018
DOI: 10.1039/c8ra06659k
|View full text |Cite
|
Sign up to set email alerts
|

pH-responsive and porous vancomycin-loaded PLGA microspheres: evidence of controlled and sustained release for localized inflammation inhibition in vitro

Abstract: pH-responsive and porous vancomycin-loaded PLGA microspheres were developed for adequate delivery of antibiotics to infected sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…Secondly, vancomycin is a hydrophilic antibiotic and is convenient to work with in aqueous media, along with being adsorbed onto HAp more effectively than its hydrophobic analogues while remaining loadable into PLGA. A number of studies have reported on the successful loading and delivery of vancomycin with the use of PLGA spheres [ 48 , 49 , 50 ]. Overall, the drug release results confirm that the addition of the HAp shell around the PLGA spheres does not impede the release from the polymer.…”
Section: Resultsmentioning
confidence: 99%
“…Secondly, vancomycin is a hydrophilic antibiotic and is convenient to work with in aqueous media, along with being adsorbed onto HAp more effectively than its hydrophobic analogues while remaining loadable into PLGA. A number of studies have reported on the successful loading and delivery of vancomycin with the use of PLGA spheres [ 48 , 49 , 50 ]. Overall, the drug release results confirm that the addition of the HAp shell around the PLGA spheres does not impede the release from the polymer.…”
Section: Resultsmentioning
confidence: 99%
“…Protonation can induce conformational changes in peptides that destabilize lipids, promoting payload release, or facilitate insertion into biological lipid membranes, enhancing endosomal escape and payload release into the cytosol [ 138 , 474 ], Acid-induced degradation of inorganics such as calcium phosphate (Ca 3 (PO 4 ) 2 ) shells or zinc oxide (ZnO) gatekeepers allow the encapsulated payloads to be released at a pH below 5.0 [ 459 ]. The CO 2 pressure that results from the acid-induced degradation of NH 4 HCO 3 has been demonstrated to be sufficient to crack polymeric shells, enhancing payload release [ 457 ]. Recent advances in the application of these techniques to the various platforms discussed in Section 2 are reviewed below.…”
Section: Stimulimentioning
confidence: 99%
“…A recent study showed that pH value can regulate drug release rate, with a more acidic pH value releasing the microsphere-entrapped drugs more quickly. 24 In the current study, the drug release rate of MMC-loaded PPM at pH 6.5 was faster than that at pH 7.4, suggesting that MMC-loaded PPM had potential for tumor targeting. A549 cells were injected subcutaneously into C57BL/6 nude mice to detect the anti-tumor function of MMCloaded PPM on tumor growth in vivo.…”
mentioning
confidence: 46%